Glass melting method based on quartz sand granularity optimization

By optimizing the particle size of quartz sand through screening, acid washing, calcination, and multi-stage grading, the problem of high impurity content in quartz sand in traditional glass production is solved, achieving high-quality, high-efficiency production and low-energy glass manufacturing.

CN120841813APending Publication Date: 2025-10-28SHAANXI TOPRAY SOLAR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511160871.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In traditional glass production, the uneven particle size distribution and high impurity content of quartz sand result in poor glass quality, low production efficiency, high energy consumption, and serious environmental pollution.

Method used

Quartz sand is screened using spectral analysis, combined with acid washing and calcination to remove impurities, and then classified in multiple stages using a laser particle size analyzer. Different pre-melting conditions are set in furnaces with different particle sizes, and nitrogen is introduced into the mixing and homogenizing furnace for stirring. The melting process is optimized to improve glass quality and production efficiency.

Benefits of technology

It improves the light transmittance and purity of glass, reduces energy consumption and production costs, reduces environmental pollution, and enhances production efficiency and product performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120841813A_ABST
    Figure CN120841813A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of glass manufacturing process optimization, and discloses a glass melting method based on quartz sand granularity optimization, which comprises the following steps: selecting quartz sand as a basic raw material, comprehensively detecting trace impurities in the quartz sand, establishing a detected impurity file, pickling the quartz sand according to the impurity file, washing with clear water, and calcining. The purity of SiO2 in the quartz sand is gt; the content of impurities such as Fe2O3 and Al2O3 is 1t; performing multi-stage screening on the quartz sand subjected to impurity removal by utilizing a laser particle size analyzer, respectively conveying the raw materials into four smelting furnaces according to the particle size multi-stage screening result and the proportion of each particle size, setting different pre-melting conditions and fluxing agent dosage, merging the pre-melts of the first three furnaces into a mixing and homogenizing furnace, and uniformly mixing the pre-melts in the mixing and homogenizing furnace; the preparation method comprises the following steps: preparing a glass melt, introducing nitrogen, mixing and stirring to obtain the glass melt, molding the glass melt through molding equipment, annealing, finally detecting the light transmittance, the bubble content and the sand grain defect of the molded glass, and optimizing and adjusting the granularity ratio or the melting condition of the next batch according to the detection result.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass manufacturing process optimization technology, specifically a glass melting method based on the optimization of quartz sand particle size. Background Art

[0002] In glass manufacturing, quartz sand is a primary raw material, and its particle size and purity have a crucial impact on glass quality and production efficiency. In traditional glass production methods, the particle size distribution of quartz sand is relatively wide, and the impurity content is high. This not only increases energy consumption during glass melting but also easily leads to problems such as bubbles and sand particle defects, affecting the light transmittance and overall quality of the glass. Furthermore, traditional processes have limited pretreatment measures for quartz sand, making it difficult to effectively remove impurities such as iron and aluminum, further restricting the improvement of glass product performance.

[0003] With the increasing demand for high-end glass products such as photovoltaic glass, the market has placed higher demands on the light transmittance, uniformity, and purity of glass. To meet these demands, it is particularly important to develop a glass melting method that can optimize the particle size distribution of quartz sand, reduce impurity content, and improve melting efficiency. Summary of the Invention

[0004] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a glass melting method based on optimized quartz sand particle size, which has the advantages of improving glass quality, reducing production costs, and reducing energy consumption and environmental pollution. It solves the problems of poor glass quality, low production efficiency, high energy consumption, and environmental pollution caused by uneven quartz sand particle size distribution and high impurity content in traditional glass production.

[0005] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: a glass melting method based on optimized quartz sand particle size, comprising the following steps: Step 1: Quartz sand raw material screening and testing: Quartz sand is selected as the basic raw material. Spectroscopic analysis technology is used to comprehensively test the trace impurities in the screened quartz sand. Then, an impurity file for the quartz sand raw material is established to record the impurity content of each batch of quartz sand. Step 2, Impurity Removal: According to the impurity file, the quartz sand is acid-washed using either hydrochloric acid or nitric acid. After acid washing, the quartz sand is rinsed with clean water and then calcined under set conditions to ensure that the SiO2 purity is >99.5% and the Fe2O3 and Al2O3 impurity content is <0.01%. Step 3: Raw material particle size classification: Use a laser particle size analyzer to perform multi-stage sieving of the impurity-removed quartz sand, and measure and record the proportion of each particle size according to the laser particle size analyzer. Step 4, Pre-melting preparation for each furnace: Based on the results of multi-stage particle size sieving and the proportion of each particle size, the raw materials are respectively transported to four furnaces A, B, C and D; Step 5, Furnace Melting Conditions: Different pre-melting conditions are set for raw materials of different particle sizes, and different amounts of flux are added accordingly for melting to obtain pre-melted materials for four furnaces: A, B, C, and D. Step 6, Melt Mixing and Bubble Removal: Combine the pre-melted materials from furnaces A, B, and C into furnace D, introduce nitrogen gas, and start the stirrer in furnace D, setting the stirring frequency to 10-15 rpm to obtain a mixed glass melt. Step 7: Shaping: The mixed glass melt is shaped using a shaping device; Step 8: Annealing: Place the formed glass into an annealing furnace for annealing treatment; Step 9, Quality Inspection: Inspect the light transmittance, bubble content, and sand particle defects of the formed glass, and optimize and adjust the particle size distribution or melting conditions for the next batch based on the inspection results.

[0006] Preferably, the impurity removal process in step two includes: selecting hydrochloric acid with a concentration of 8% to 12% or nitric acid with a concentration of 5% to 10%.

[0007] Preferably, in step two, the rinsing and calcination process involves rinsing the acid-washed quartz sand with clean water 3 to 8 times, and then calcining the rinsed quartz sand at a temperature of 600-650℃ for 1.5 to 2 hours.

[0008] Preferably, the particle size classification and proportion of quartz sand in step three are as follows: (1) Coarse particles with D50 > 80 μm account for 8% to 10%; (2) Medium particles with D50 = 48 μm account for 70% to 80%; (3) Fine particles with D50 < 10 μm account for 10% to 15%; (4) The mixed particles have a D50 between 10-80 μm and account for 2% to 5%.

[0009] Preferably, in step four, the furnaces are divided into three pre-melting furnaces: A, B, and C, each with a volume of 1-2 cubic meters; and furnace D, a mixing and homogenizing furnace with a volume of 5-8 cubic meters. Furnaces A, B, and C are all interconnected with furnace D.

[0010] Preferably, in step four, the pre-melting preparation uses furnace A for medium-particle quartz sand raw material; furnace B for coarse-particle quartz sand raw material; furnace C for fine-particle quartz sand raw material; and furnace D for mixed-particle quartz sand raw material.

[0011] Preferably, the furnace melting conditions in step five are as follows: (1) Furnace A: Add flux accounting for 4% to 6% of the mass of the granular raw material in the quartz sand, raise the temperature from room temperature to 1200-1250℃ at a rate of 30-40℃ / min, and hold for 2 to 2.5 hours; (2) Furnace B: Add flux accounting for 8% to 12% of the mass of coarse quartz sand raw material, heat to 1350-1400℃ at a rate of 55-60℃ / min, then accelerate the heating rate to 10℃ / min, and control the pre-melting process time to 1.5 to 2 hours: (3) C furnace: Add flux accounting for 3% to 4% of the mass of fine quartz sand raw material, heat to 1100-1150℃ at a rate of 35-40℃ / min, and hold for 3 to 4 hours; (4) D furnace: Add flux accounting for 3% to 5% of the mass of the quartz sand mixed particles, heat to 1250-1350℃ at a rate of 45-50℃ / min, and keep warm for 3 to 4 hours.

[0012] Preferably, in step six, the bubble removal involves combining the melts from furnaces A, B, and C into furnace D, introducing nitrogen gas at a flow rate of 5–10 L / min, and stirring at a frequency of 10–15 rpm.

[0013] Preferably, the molding temperature in step seven is controlled at 1000℃-1100℃.

[0014] Preferably, the annealing conditions in step eight are: the annealing temperature is set at 500℃-600℃, and the annealing time is 2-3 hours.

[0015] Compared with existing technologies, this invention provides a glass melting method based on optimized quartz sand particle size, which has the following beneficial effects: 1. This invention aims to improve glass quality by optimizing the particle size of quartz sand and treating impurities. It utilizes spectral analysis to comprehensively detect impurities in the quartz sand and combines this with pretreatment processes such as acid washing and calcination to remove impurities, thereby reducing the content of iron, aluminum, and other trace impurities in the glass raw materials and increasing the purity of silica. Simultaneously, a laser particle size analyzer is used to perform multi-stage particle size classification of the quartz sand, followed by pre-melting in separate furnaces based on the particle size distribution. This results in a final glass melt with uniform particle size distribution, reduced internal stress, increased light transmittance, and a significant reduction in bubble content and sand particle defects, thus improving the overall quality of the glass.

[0016] 2. This invention achieves the beneficial effects of improving production efficiency and reducing energy consumption by optimizing the melting process and the melt mixing process. By setting different pre-melting conditions for quartz sand of different particle sizes, and accelerating the uniform mixing of molten glass in the mixing and homogenizing furnace by introducing nitrogen and stirring, internal defects in the melt are effectively reduced, the melting time of quartz sand is shortened, and resource consumption during the melting process is reduced by precisely controlling the heating rate and holding time of each furnace and optimizing the amount of flux. Thus, while improving glass production efficiency, carbon emissions during glass production are also reduced. Attached Figure Description

[0017] Figure 1 This is the method flow of the present invention. Detailed Implementation

[0018] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0019] Please see Figure 1 A glass melting method based on optimized quartz sand particle size includes the following steps: Step 1: Quartz sand raw material screening and testing: Quartz sand is selected as the basic raw material. Spectroscopic analysis technology is used to comprehensively test the trace impurities in the screened quartz sand. The impurity content includes iron, aluminum, calcium, and other impurity elements that affect glass quality. Then, an impurity file for quartz sand raw material testing is established to record the impurity content of each batch of quartz sand. Step 2, Impurity Removal: According to the impurity file, the quartz sand is acid-washed using hydrochloric acid (HCl) or nitric acid (HNO3) to remove metallic impurities. Waste acid can be reused or neutralized with lime (pH adjusted to 8-9) before discharge to avoid secondary pollution. The acid-washed quartz sand is rinsed with clean water and then calcined under set conditions to ensure that the SiO2 purity is >99.5% and the Fe2O3 and Al2O3 impurity content is <0.01%, ensuring that the purity of the quartz sand raw material entering the raw material particle size classification process meets the standards. Step 3: Raw material particle size classification: Use a laser particle size analyzer to perform multi-stage sieving of the impurity-removed quartz sand (e.g., coarse particles > 80 μm, medium particles 48 μm, fine particles < 10 μm), and measure and record the proportion of each particle size according to the laser particle size analyzer. Step 4, Pre-melting preparation for each furnace: Based on the results of multi-stage particle size sieving and the proportion of each particle size, the raw materials are respectively transported to four furnaces A, B, C and D; Step 5, Furnace Melting Conditions: Different pre-melting conditions are set for raw materials of different particle sizes, and different amounts of flux are added accordingly for melting to obtain pre-melted materials for four furnaces: A, B, C, and D. Step 6, Melt Mixing and Bubble Removal: Combine the pre-melted glass from furnaces A, B, and C into furnace D, introduce nitrogen gas, and start the stirrer in furnace D (such as a mechanical paddle or airflow disturbance). Set the stirring frequency to 10-15 rpm to accelerate the uniform mixing of the molten glass, reduce internal stress in the melt by ensuring a uniform particle size distribution, improve the light transmittance of the photovoltaic glass, and obtain a uniformly mixed glass melt. Step 7: Shaping: The mixed glass melt is shaped using a shaping device; Step 8: Annealing: Place the formed glass into an annealing furnace for annealing treatment; Step 9, Quality Inspection: Inspect the light transmittance (spectrophotometer), bubble content (ultrasonic testing), and sand particle defects (microscopic observation) of the formed glass. Based on the test results, optimize and adjust the particle size distribution (e.g., increase the proportion of fine particles by 5%) or melting conditions (fluctuation range ±10℃, amount of flux) for the next batch.

[0020] Specifically, the impurity removal process in step two includes selecting hydrochloric acid (HCl) with a concentration of 8% to 12% or nitric acid (HNO3) with a concentration of 5% to 10%. This concentration range helps to reduce the corrosion of quartz sand and preserve the integrity of the SiO2 crystal phase.

[0021] Specifically, in step two, the rinsing and calcination process involves rinsing the acid-washed quartz sand 3 to 8 times with clean water to remove residual acid. The rinsed quartz sand is then calcined at 600-650℃ for 1.5 to 2 hours to remove organic matter, thereby eliminating raw materials with excessive impurities.

[0022] Specifically, the particle size classification and proportion of quartz sand in step three are as follows: (1) Coarse particles with D50 > 80 μm account for 8% to 10%; (2) Medium particles D50=48μm, accounting for 70%~80% (optimal particle size); (3) Fine particles with D50 < 10 μm account for 10% to 15%; (4) The mixed particles D50 is between 10-80μm, accounting for 2% to 5%. The unscreened particles stick together due to humidity or other reasons, but the particle size is less than 80μm.

[0023] The advantages are: by optimizing the particle size of quartz sand and treating impurities, the quality of glass can be improved. Spectroscopic analysis technology is used to comprehensively detect impurities in the quartz sand, and impurity removal is carried out in combination with pretreatment processes such as acid washing and calcination to reduce the content of iron, aluminum, and other trace impurities in the glass raw materials, thereby improving the purity of silica. At the same time, a laser particle size analyzer is used to classify the quartz sand into multiple grades, and then pre-melting is carried out in separate furnaces according to the particle size distribution. This results in a uniform particle size distribution in the final glass melt, reduced internal stress, increased light transmittance, and a significant reduction in bubble content and sand particle defects, thus improving the overall quality of the glass.

[0024] Specifically, in step four, the furnaces are divided into three pre-melting furnaces: A, B, and C, with a single furnace volume of 1-2 cubic meters; and furnace D, a mixing and homogenizing furnace with a volume of 5-8 cubic meters. Furnaces A, B, and C can all be connected to furnace D to facilitate subsequent mixing and homogenizing operations.

[0025] Specifically, in step four, the pre-melting preparation is as follows: medium-particle quartz sand raw material is prepared using furnace A; coarse-particle quartz sand raw material is prepared using furnace B; fine-particle quartz sand raw material is prepared using furnace C; and mixed-particle quartz sand raw material is prepared using furnace D.

[0026] Specifically, the melting conditions in step five are as follows: (1) Furnace A: Add flux accounting for 4% to 6% of the mass of the granular raw material in the quartz sand, raise the temperature from room temperature to 1200-1250℃ at a rate of 30-40℃ / min, and keep it at that temperature for 2 to 2.5 hours to promote the complete melting of the medium-sized quartz sand and ensure the uniformity of the melt. (2) B furnace: Add flux accounting for 8% to 12% of the mass of coarse quartz sand raw material, heat to 1350-1400℃ at a rate of 55-60℃ / min, then accelerate the heating rate to 10℃ / min, and rapidly heat to the glass melt formation temperature. Utilize the vortex effect in the furnace to promote the gradual melting of coarse particles. The pre-melting process time is controlled at 1.5 to 2 hours. (3) C furnace: Add flux accounting for 3% to 4% of the mass of fine quartz sand raw material, heat to 1100-1150℃ at a rate of 35-40℃ / min, and hold for 3 to 4 hours to ensure that the fine particles are completely melted and reduce unmelted residue; (4) D furnace: Add flux accounting for 3% to 5% of the mass of the mixed quartz sand particles, heat to 1250-1350℃ at a rate of 45-50℃ / min, and keep warm for 3 to 4 hours to ensure that the mixed quartz sand particles are melted evenly.

[0027] Specifically, in step six, bubble removal involves combining the melts from furnaces A, B, and C into furnace D, introducing nitrogen gas at a flow rate of 5–10 L / min, and stirring at a frequency of 10–15 rpm to promote bubble removal.

[0028] Specifically, in step seven, the forming temperature is controlled at 1000℃-1100℃ to ensure good fluidity of the molten glass and uniform thickness of the formed glass.

[0029] Specifically, in step eight, the annealing conditions are as follows: the annealing temperature is set at 500℃-600℃, and the annealing time is 2-3 hours. The purpose is to eliminate the internal stress of the glass and prevent cracks or deformations from occurring during subsequent use.

[0030] The advantages are: by optimizing the melting process and the melt mixing process, the production efficiency can be improved and the energy consumption reduced. By setting different pre-melting conditions for quartz sand of different particle sizes, and by introducing nitrogen and stirring in the mixing and homogenizing furnace to accelerate the uniform mixing of the glass melt, internal defects in the melt can be effectively reduced and the melting time of the quartz sand can be shortened. Furthermore, by precisely controlling the heating rate and holding time of each furnace and optimizing the amount of flux, resource consumption during the melting process can be reduced. Thus, while improving glass production efficiency, carbon emissions during the glass production process can also be reduced.

[0031] The following are six melting scenarios for glass production using quartz sand. Examples 1-3 employ the method of this invention, while Comparative Examples 1-3 serve as control groups for the method of this invention. Example 1 Scenario 1: Ten tons of quartz sand were selected as raw material. Spectroscopic analysis was used to detect impurities, revealing high levels of iron, aluminum, and calcium impurities. Based on the impurity profile, the quartz sand was acid-washed with 10% hydrochloric acid. The waste acid was neutralized with lime (pH adjusted to 8-9) before being discharged. The acid-washed quartz sand was rinsed five times with clean water and then calcined at 620℃ for 1.8 hours. Secondary testing showed that the SiO2 purity reached 99.6%, and the iron and aluminum impurity contents were both below 0.01%. A laser particle size analyzer was then used for classification, yielding coarse particles (D50>80μm) accounting for 9%, medium particles (D50=48μm) accounting for 75%, fine particles (D50<10μm) accounting for 13%, and mixed particles (D50 between 10-80μm) accounting for 3%.

[0032] Comparative Example 1 Scenario 2: Similarly, 10 tons of quartz sand raw material were selected, but only water rinsing was used without acid washing and high-temperature calcination. The test found that the purity of SiO2 was only 99.2%, and the content of iron and aluminum impurities exceeded 0.05%. After particle size classification, the particle distribution was chaotic, and the particle ratio was only 60% in the test. Moreover, the impurities caused more sand particle defects in subsequent glass production, and the product qualification rate was greatly reduced.

[0033] Example 2

[0034] Comparative Example 2 Scenario 4: Using the traditional mixed melting method, the particles are melted uniformly without differentiation. Flux with the corresponding proportion of raw materials is added, and the temperature is raised to 1300℃ at a fixed heating rate. The forming and annealing processes are the same, but the light transmittance of the photovoltaic glass produced is only increased by 0.3%, the glass contains a lot of bubbles, and the sand defects are obvious due to the incomplete melting of coarse particles, which seriously affects the product quality and performance.

[0035] Example 3 Scenario 5: Applying the method of this invention to a production line with an annual output of 100,000 tons of high-purity sand, the cost per ton of high-purity sand is reduced by 80 yuan through particle size optimization, resulting in annual cost savings of 8 million yuan. During the production process, low-energy silica sand purification technology is adopted, which reduces carbon emissions by 30% compared with traditional processes. At the same time, the tailings recycling rate reaches 80%, reducing raw material procurement costs by 12%. After the photovoltaic glass produced is used in modules, the defect rate of silicon wafer cutting is reduced by 2%, the overall cost of photovoltaic modules is reduced, and the added value of products is greatly increased.

[0036] Comparative Example 3 Scenario 6: The same production line as Example 3 uses traditional processes, without particle size optimization and tailings recycling. The cost per ton is not significantly reduced, carbon emissions are high, and the silicon wafer cutting defect rate is high due to glass quality issues. The module power generation efficiency is low, the overall production cost is high, and the economic and environmental benefits are far lower than those of Example 3.

[0037] In summary, through the above six scenario examples and comparative examples, it can be seen that the granularity optimization method of this invention has achieved significant results in reducing production costs, improving the light transmittance of photovoltaic glass, meeting the needs of large-scale production, and promoting environmental protection and sustainable development.

[0038] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A glass melting method based on optimized quartz sand particle size, characterized in that, The following steps are involved: Step 1: Quartz sand raw material screening and testing: Quartz sand is selected as the basic raw material. Spectroscopic analysis technology is used to comprehensively test the trace impurities in the screened quartz sand. Then, an impurity file for the quartz sand raw material is established to record the impurity content of each batch of quartz sand. Step 2, Impurity Removal: According to the impurity file, the quartz sand is acid-washed using either hydrochloric acid or nitric acid. After acid washing, the quartz sand is rinsed with clean water and then calcined under set conditions to ensure that the SiO2 purity is >99.5% and the Fe2O3 and Al2O3 impurity content is <0.01%. Step 3: Raw material particle size classification: Use a laser particle size analyzer to perform multi-stage sieving of the impurity-removed quartz sand, and measure and record the proportion of each particle size according to the laser particle size analyzer. Step 4, Pre-melting preparation for each furnace: Based on the results of multi-stage particle size sieving and the proportion of each particle size, the raw materials are respectively transported to four furnaces A, B, C and D; Step 5, Furnace Melting Conditions: Different pre-melting conditions are set for raw materials of different particle sizes, and different amounts of flux are added accordingly for melting to obtain pre-melted materials for four furnaces: A, B, C, and D. Step 6, Melt Mixing and Bubble Removal: Combine the pre-melted materials from furnaces A, B, and C into furnace D, introduce nitrogen gas, and start the stirrer in furnace D, setting the stirring frequency to 10-15 rpm to obtain a mixed glass melt. Step 7: Shaping: The mixed glass melt is shaped using a shaping device; Step 8: Annealing: Place the formed glass into an annealing furnace for annealing treatment; Step 9, Quality Inspection: Inspect the light transmittance, bubble content, and sand particle defects of the formed glass, and optimize and adjust the particle size distribution or melting conditions for the next batch based on the inspection results.

2. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, The impurity removal process in step two includes: selecting hydrochloric acid with a concentration of 8% to 12% or nitric acid with a concentration of 5% to 10%.

3. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, In step two, the rinsing and calcination process is as follows: the acid-washed quartz sand is rinsed with clean water 3 to 8 times, and the rinsed quartz sand is calcined at a temperature of 600-650℃ for 1.5 to 2 hours.

4. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, The particle size distribution and proportion of quartz sand in step three are as follows: (1) Coarse particles with D50 > 80 μm account for 8% to 10%; (2) Medium particles with D50 = 48 μm account for 70% to 80%; (3) Fine particles with D50 < 10 μm account for 10% to 15%; (4) The mixed particles have a D50 between 10-80 μm and account for 2% to 5%.

5. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, The furnace division in step four includes: three furnaces A, B and C are pre-melting furnaces, with a single furnace volume of 1-2 cubic meters; furnace D is a mixing and homogenization furnace with a volume of 5-8 cubic meters; and furnaces A, B and C can be interconnected with furnace D.

6. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, In step four, the pre-melting preparation is as follows: medium-particle quartz sand raw material is prepared using furnace A; coarse-particle quartz sand raw material is prepared using furnace B; fine-particle quartz sand raw material is prepared using furnace C; and mixed-particle quartz sand raw material is prepared using furnace D.

7. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, The furnace melting conditions in step five are as follows: (1) Furnace A: Add flux accounting for 4% to 6% of the mass of the granular raw material in the quartz sand, raise the temperature from room temperature to 1200-1250℃ at a rate of 30-40℃ / min, and hold for 2 to 2.5 hours; (2) Furnace B: Add flux accounting for 8% to 12% of the mass of coarse quartz sand raw material, heat to 1350-1400℃ at a rate of 55-60℃ / min, then accelerate the heating rate to 10℃ / min, and control the pre-melting process time to 1.5 to 2 hours: (3) C furnace: Add flux accounting for 3% to 4% of the mass of fine quartz sand raw material, heat to 1100-1150℃ at a rate of 35-40℃ / min, and hold for 3 to 4 hours; (4) D furnace: Add flux accounting for 3% to 5% of the mass of the quartz sand mixed particles, heat to 1250-1350℃ at a rate of 45-50℃ / min, and keep warm for 3 to 4 hours.

8. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, In step six, bubble removal involves combining the melts from furnaces A, B, and C into furnace D, introducing nitrogen gas at a flow rate of 5–10 L / min, and stirring at a frequency of 10–15 rpm.

9. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, In step seven, the molding temperature is controlled at 1000℃-1100℃.

10. The glass melting method based on quartz sand particle size optimization according to claim 1, characterized in that, The annealing conditions in step eight are as follows: the annealing temperature is set at 500℃-600℃, and the annealing time is 2-3 hours.